Exploring Performances of LGBTQ Sexualities in Irish Primary Schools - Horgan, Darragh (STER, 2020)
This research set out to explore the performances of LGBTQ (lesbian, gay, bisexual, trans and queer) sexualities in a selection of Irish Primary Schools in 2019, looking specifically at how performances of sexuality are negotiated by teachers. Performances of sexuality are examined with a lens of authenticity and a specific focus on four key anchors that influence how LGBTQ teachers perform their sexuality in an educational context: security of tenure, school climate, authentic disclosures and authentic performances.
Journal article.
Keywords: Research Subject Categories::SOCIAL SCIENCES; Sexuality; Performance; Queer Pedagogy; Primary Education